2000
DOI: 10.1523/jneurosci.20-15-05715.2000
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Mitochondrial Dysfunction in Excitotoxic Neuron Death: CytochromecRelease and a Secondary Increase in Superoxide Production

Abstract: An increased production of superoxide has been shown to mediate glutamate-induced neuron death. We monitored intracellular superoxide production of hippocampal neurons during and after exposure to the glutamate receptor agonist NMDA (300 microm). During a 30 min NMDA exposure, intracellular superoxide production increased significantly and remained elevated for several hours after wash-out of NMDA. After a 5 min exposure, superoxide production remained elevated for 10 min, but then rapidly returned to baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
171
1
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(184 citation statements)
references
References 58 publications
(80 reference statements)
8
171
1
4
Order By: Relevance
“…Conversely, if the ATP demand is less severe and the capacity of cells to generate ATP is sufficient, neurons restore their ionic gradients, and only a transient decrease in mitochondrial membrane potential ( m ) or cellular ATP levels can be detected. Nevertheless, many of these neurons proceed to undergo apoptotic death over the following hours Bonfoco et al, 1995;Luetjens et al, 2000;Ward et al, 2007).…”
Section: Bim Mediates Excitotoxic Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, if the ATP demand is less severe and the capacity of cells to generate ATP is sufficient, neurons restore their ionic gradients, and only a transient decrease in mitochondrial membrane potential ( m ) or cellular ATP levels can be detected. Nevertheless, many of these neurons proceed to undergo apoptotic death over the following hours Bonfoco et al, 1995;Luetjens et al, 2000;Ward et al, 2007).…”
Section: Bim Mediates Excitotoxic Apoptosismentioning
confidence: 99%
“…Stimulation of glutamate receptors in cerebellar granular neurons (CGNs) with 100 µM glutamate/10 µM Gly for 10 min resulted in a delayed excitotoxic apoptosis within a 4-24-h time frame, which was characterized by cell shrinkage and nuclear pyknosis ( outer membrane permeabilization in excitotoxic apoptosis Budd et al, 2000;Luetjens et al, 2000;Ward et al, 2000Ward et al, , 2006Wang et al, 2004;Cheung et al, 2005). We next investigated whether the loss of Bim expression modulated these events.…”
Section: Bh3-only Protein Bimmentioning
confidence: 99%
See 1 more Smart Citation
“…SOD was used to demonstrate specificity of MPP + -induced ROS, which can be scavenged by SOD treatment. We and others have shown addition of exogenous SOD or the cell permeable SOD mimetic MnTBAP attenuated both generation of ROS and apoptosis in neuronal cells (Drukarch et al, 1998;Choi et al, 1999;Luetjens et al, 2000;Kitazawa et al, 2001;Anantharam et al, 2002;Kaul et al, 2003); hence, we used SOD not as an NADPH oxidase inhibitor but as a ROS inhibitor. Using flow cytometric analysis with the ROS-sensitive fluorescence probe hydroethidine, we show that the NADPH oxidase inhibitor AEBSF significantly blocked MPP + -induced increases in ROS production.…”
Section: Nadph Oxidase Inhibitor Significantly Blocks Mpp + -Induced mentioning
confidence: 99%
“…14 Overstimulation of ionotropic glutamate receptors (iGluR), namely N-methyl-D-aspartate (NMDA) receptors, provokes pathophysiological increases in intracellular Ca 2ϩ and consequently leads to the activation of several overlapping Ca 2ϩ -dependent processes, such as the generation of mitochondrial reactive oxygen species and loss of cellular viability. [15][16][17][18][19][20] DOM has been shown to be 8 to 10 times more potent than kainic acid in rodents, producing a similar reproducible pattern of behavioral toxicity culminating in seizures. 8,21,22 Studies conducted in rats, mice, and cynomolgus monkeys have shown a consistent pattern of DOM-induced damage to the hippocampal pyramidal neurons, as well as to the thalamic, amygdalar, entorhinal, cortical, and septal neurons after DOM administration (0.22 to 4.4 mg/kg i.p.).…”
mentioning
confidence: 99%